Translation Techniques Used for Translating Cultural Aspects in the Television Series "Cigarette Girl" - Damarratri, Hayuning Sekar; Afifulloh, M (Loquēla (Journal of Linguistics, Literature, and Education), 2024)
“Cigarette Girl” is an Indonesian television series that showcases many Javanese cultures. This series has been aired globally on a popular streaming platform, Netflix. As depicting various cultural aspects, this series has a clear and concise subtitle translation in English to make the story plot understandable for foreign audiences. Therefore, translation techniques were potentially used to create a good subtitle for the series. In this case, this research aimed to identify the cultural aspects portrayed in the series and the techniques used to translate them. It involved a qualitative approach to produce a comprehensive analysis discussion. Based on the analysis conducted, the presence of various Javanese cultural terms contained in the series was revealed, including mas, rama, ibu, bapak, jeng, mbak/mbak ayu/mbakyu, yu, ndhuk, nyi, cah ayu, kretek, srintil, tingwe, saus, pelinting, sendika, dong, nginthil, monggo, toh, mawon, macak, manak, gusti paringana aku, and dalang. Seven translation techniques were also found to be used to translate those cultural terms. They were adaptation, calque, generalisation, reduction, borrowing, description, and addition.